2017
DOI: 10.2340/00015555-2503
|View full text |Cite
|
Sign up to set email alerts
|

Normal Skin Microbiota is Altered in Pre-clinical Hidradenitis Suppurativa

Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease defined by recurrent nodules, tunnels (sinus tracts) and scarring involving the intertriginous regions. The clinical course of HS is compatible with a biofilm-driven disease, and biofilm has been described in lesional HS skin. We therefore hypothesized that clinically unaffected HS skin would also have an increased presence of biofilm compared with that of healthy controls. We conducted a case-control study, investigating the morphology of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 43 publications
3
90
0
2
Order By: Relevance
“…As previously suggested, this lack of Propionibacterium spp. may potentially provide a cutaneous dysbiosis in the early stages of the pathogenesis in HS . The potential reduced number of sebaceous glands and subsequent reduced secretion of sebum in intertriginous HS regions may potentially lead to a shift in the local microbial community of hair follicles .…”
Section: Discussionmentioning
confidence: 99%
“…As previously suggested, this lack of Propionibacterium spp. may potentially provide a cutaneous dysbiosis in the early stages of the pathogenesis in HS . The potential reduced number of sebaceous glands and subsequent reduced secretion of sebum in intertriginous HS regions may potentially lead to a shift in the local microbial community of hair follicles .…”
Section: Discussionmentioning
confidence: 99%
“…Studies report prevalence rates of HS from 1% to 4% in European populations, with females more frequently affected than males . Although the pathogenesis remains enigmatic, studies have suggested the combination of occlusion of the hair follicles and a dysfunctional immune response leading to chronic inflammation, with a presumed contribution of the intertriginous bacterial microbiome …”
Section: Introductionmentioning
confidence: 99%
“…Microbiological studies in HS patients have shown primarily skin or intestinal (especially in the anogenital area), anaerobic commensals in lesional HS tissue . Data suggest a shift in microbiota from preclinical paucity to an abundance in chronic lesions . An aberrant interaction between the commensal skin bacteria and the skin immune system has been suggested to play a role in HS.…”
Section: Discussionmentioning
confidence: 99%
“…Hidradenitis Suppurativa (HS) is a chronic, debilitating skin disease characterized by recurrent abscesses, nodules, sinuses and scarring involving the intertriginous areas of the body . Although HS is not considered to be a simple infection, bacteria are thought to play a role in the pathogenesis and an aberrant interaction of commensal skin bacteria with the innate skin immune system in patients with HS has been suggested as a central element of the pathogenesis of the disease . This implies that both immune system and the commensal flora of HS patients may have functional characteristics which influence the pathogenesis of HS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation